2016
DOI: 10.1080/13561820.2016.1233096
|View full text |Cite
|
Sign up to set email alerts
|

The Interprofessional Collaborative Competency Attainment Survey (ICCAS): A replication validation study

Abstract: This study replicates a validation of the Interprofessional Collaboration Competency Attainment Survey (ICCAS), a 20-item self-report instrument designed to assess behaviours associated with patient-centred, team-based, collaborative care. We appraised the content validity of the ICCAS for a foundation course in interprofessional collaboration, investigated its internal (factor) structure and concurrent validity, and compared results with those obtained previously by ICCAS authors. Self-assessed competency rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
139
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(148 citation statements)
references
References 14 publications
8
139
1
Order By: Relevance
“…The ICCAS aligns with the IPEC competencies 17 and has excellent evidence of validity. 29 In the same study, factor analysis provided evidence of construct validity as did mean rating diferences from pretest to posttest for each pre-experience and post-experience item pair on the ICCAS. 29 In the same study, factor analysis provided evidence of construct validity as did mean rating diferences from pretest to posttest for each pre-experience and post-experience item pair on the ICCAS.…”
Section: Methodsmentioning
confidence: 87%
“…The ICCAS aligns with the IPEC competencies 17 and has excellent evidence of validity. 29 In the same study, factor analysis provided evidence of construct validity as did mean rating diferences from pretest to posttest for each pre-experience and post-experience item pair on the ICCAS. 29 In the same study, factor analysis provided evidence of construct validity as did mean rating diferences from pretest to posttest for each pre-experience and post-experience item pair on the ICCAS.…”
Section: Methodsmentioning
confidence: 87%
“…[22][23][24] A revised version of the ICCAS uses the same 20 items but with responses on a ive-point scale from 1=poor to 5=excellent; this tool was also found to have content validity. 25 Either test is administered in one sitting, by the use of a test-retest design for which responses are completed retrospectively. [21][22][23][24][25] For either version of the test, upon relection, participants respond to how they felt about each item before exposure to an IPE experience and then again when considering how they felt after participating in an IPE event.…”
Section: Post-ipe Activity Surveysmentioning
confidence: 99%
“…25 Either test is administered in one sitting, by the use of a test-retest design for which responses are completed retrospectively. [21][22][23][24][25] For either version of the test, upon relection, participants respond to how they felt about each item before exposure to an IPE experience and then again when considering how they felt after participating in an IPE event. Both versions of the ICCAS evaluate participants' self-perceived increase in attainment of interprofessional competencies.…”
Section: Post-ipe Activity Surveysmentioning
confidence: 99%
See 1 more Smart Citation
“…9 This validated pre-post survey consists of 20 items that ask respondents to assess their interprofessional competencies (e.g., communication, collaboration, roles and responsibilities, collaborative patient/ family-centered approach, conflict management/ resolution, and team functioning). 10 Some studies have reported that health professions students had improved ICCAS scores from pretest to posttest following their IPE experience, which suggested an effective IPE strategy could help students develop interprofessional competence. [11][12][13][14] In these teaching activities, it is very important to engage students in IPE and influence their attitudes towards this method because negative attitudes can hinder learning via IPE.…”
mentioning
confidence: 99%